The Bank Lending Channel of Monetary Policy in Nepal: Evidence from Bank Level Data - Budha, Birendra Bahadur (NRB Economic Review, 2013)
This paper examines the bank lending channel of monetary policy transmission in Nepal using data during 2003-2012. Using the dynamic Arellano-Bond GMM estimation with annual data of 25 Nepalese commercial banks, this study tries to estimate the loan supply responses of Nepalese commercial banks, depending on their balance sheet characteristics. The main results suggest that banks play a role in Nepal's monetary transmission mechanism. Empirical result shows that the bank lending decreases after a monetary tightening. Bank size is found to have significant impact on loan supply in Nepal. Similarly, liquidity in the case of private sector banks is also playing a significant role in bank lending in response to monetary policy changes. But, capitalization is found to have no significant impact on bank lending. The bank loan supply is also found to be significantly affected by gross domestic product.